TINGKAT PENGETAHUAN TENTANG PERATURAN PADA PERMAIAN RUGBY UNION DI UKM RUGBY UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI BOJONEGORO TAHUN 2016 - Hilmi Alriad; Rahmad Irsyada; Syaifuddin Syaifuddin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2016)
The purpose of this study was to study high-level knowledge of Rugby University, Nahdlatul Ulama University, Sunan Giri Bojonegoro in 2016 about the rules of the Rugby Union game. This research is a descriptive research. The method used is a survey with data collection techniques using true and false tests. The research instrument trials were conducted on 9 students. The subjects of this study were 9 students who were members of the Nahdlatul Ulama Sunan Giri Bojonegoro University of SMEs in 2016. Data was collected from April 10 to July 17, 2016. Data analysis techniques used descriptive analysis as outlined in the form of findings. Based on the research results needed to study the rules of the game Rugby Union Rugby Nahdlatul Ulama University Sunan Giri Bojonegoro in 2016 in the high category of 79.00%, in the medium category 66.00%, in the low category weighing 57.00%.